2022
DOI: 10.1186/s13634-022-00938-4
|View full text |Cite
|
Sign up to set email alerts
|

An efficient computation of discrete orthogonal moments for bio-signals reconstruction

Abstract: Bio-signals are extensively used in diagnosing many diseases in wearable devices. In signal processing, signal reconstruction is one of the essential applications. Discrete orthogonal moments (DOMs) are effective analysis tools for signals that can extract digital information without redundancy. The propagation of numerical errors is a significant challenge for the computation of DOMs at high orders. This problem damages the orthogonality property of these moments, which restricts the ability to recover the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The results also outperform the introduced algorithm compared to FrGLMs-HM at each order in terms of PSNR and MSE. A comparative investigation of other existing algorithms [8,18,20,36] in reconstruction quality is summarized in Table 4. Figures 7 and 8 A comparative investigation of other existing algorithms [8,18,20,36] in reconstruction quality is summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results also outperform the introduced algorithm compared to FrGLMs-HM at each order in terms of PSNR and MSE. A comparative investigation of other existing algorithms [8,18,20,36] in reconstruction quality is summarized in Table 4. Figures 7 and 8 A comparative investigation of other existing algorithms [8,18,20,36] in reconstruction quality is summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Hosny et al [15] suggested an efficient Algorithm for the compression of different types of bio-medical signals based on discrete Tchebichef moments and the Artificial Bee Colony (ABC). Fathi et al [16][17][18] introduced different algorithms based on different types of DOMs for the efficient energy compression of bio-medical signals: ECG and FPCG. Such algorithms reveal high superiority concerning remote healthcare monitoring systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The STM32f429 discovery system comprises an ARM Cortex-M4base 32-bit microcontroller from STMicroelectronics. It operates at a maximum frequency of 180 MHz, which this study utilizes for data compression [27]. The development board offers a direct memory access technique (DMA) for fPCG measuring devices accessing memory directly.…”
Section: Energy Consumption Evaluationmentioning
confidence: 99%
“…The superiority in Compression time, Compression speed, and computational efficiency are thanks to using a recurrence relation completely independent of Charlier polynomials computation, which is no longer dependent on the factorial and power functions. In addition, using HOM in the proposed algorithm leads to speeding the compression, which is considered the best way of QR decomposition in signal reconstruction quality and execution time [27].…”
Section: Energy Consumption Evaluationmentioning
confidence: 99%